2015
DOI: 10.1099/mic.0.000077
|View full text |Cite
|
Sign up to set email alerts
|

Identification of self-growth-inhibiting compounds lauric acid and 7-(Z)-tetradecenoic acid from Helicobacter pylori

Abstract: Helicobacter pylori growth medium is usually supplemented with horse serum (HS) or FCS. However, cyclodextrin derivatives or activated charcoal can replace serum. In this study, we purified self-growth-inhibiting (SGI) compounds from H. pylori growth medium. The compounds were recovered from porous resin, Diaion HP-20, which was added to the H. pylori growth medium instead of known supplements. These SGI compounds were also identified from 2,6-di-O-methyl-b-cyclodextrin, which was supplemented in a pleuropneum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…One well-characterized DSF is 2-(Z)-tetradecenoic acid (TDA) produced by the xylem-limited plant pathogen Xylella fastidiosa (Ryan and Dow, 2011; Ryan et al, 2015). Recently, Yamashita et al reported two self-growth-inhibiting compounds in Hp and one of them was identified as 7-(Z)-TDA (Yamashita et al, 2015). Although it has not been reported as a DSF, 2-(Z)-TDA is a positional isomer of 7-(Z)-TDA.…”
Section: Genetic Regulatory Pathways Of Hp Biofilm Formationmentioning
confidence: 99%
“…One well-characterized DSF is 2-(Z)-tetradecenoic acid (TDA) produced by the xylem-limited plant pathogen Xylella fastidiosa (Ryan and Dow, 2011; Ryan et al, 2015). Recently, Yamashita et al reported two self-growth-inhibiting compounds in Hp and one of them was identified as 7-(Z)-TDA (Yamashita et al, 2015). Although it has not been reported as a DSF, 2-(Z)-TDA is a positional isomer of 7-(Z)-TDA.…”
Section: Genetic Regulatory Pathways Of Hp Biofilm Formationmentioning
confidence: 99%
“…A number of free fatty acids (FFAs), with potent antibacterial activities against a broad range of bacteria (18)(19)(20)(21), including H. pylori, are of considerable research interests. In particular, FFAs seem to induce no acquired resistance to the antibacterial effect and are considered safe, which make them attractive as antibacterial agents for commercial exploitation.…”
mentioning
confidence: 99%
“…There is currently no evidence for the ability of TDA to be able to activate gene expression, and it is assumed that only cis-2-unsaturated acids (C x :Δ 2 ) has such activity (34,44). The studies conducted by Ionescu et al (38) showed that in X. fastidiosa cis-2-tetradecenic acid (C 14 :Δ 2 , XfDSF) and cis-2-hexadecenic acid (C 16 :Δ 2 , XfDSF2) are the strongest gene expression activators.…”
Section: Communication Of Microorganisms Via Diffusible Signal Factorsmentioning
confidence: 99%
“…autoaggregative behavior and biofilm formation (35,38,39,45,46). Reduction of DSFs activity and an increase in AI-2 concentration results in the transformation of some coccoid H. pylori forms to the spiral morphotype, followed by chemorepulsion from the AI-2 source and migration in search of new niches in the gastric environment (6,17,(30)(31)(32)44).…”
Section: The Holistic Model Of H Pylori Infectionmentioning
confidence: 99%
See 1 more Smart Citation